PERANCANGAN SOFT STARTING PADA MOTOR INDUKSI SATU FASA - Muhammad Zaki; Nurhazizah Nurhazizah; Zanu Saputra; Yudhi Yudhi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Induction motors have a problem that is very detrimental to the system, namely their high starting current when turned on directly. Efforts to reduce the large initial currents required a soft starting method. Soft Starting aims to get a low starting current and a smoother motor rotation. The Soft Starting method will regulate the voltage and current into the induction motor by providing a triggering angle on the TRIAC which is regulated by the Arduino platform by applying the Fuzzy Logic control system. This Fuzzy Logic method uses one input "time" and one "dimmer" output. The results of the design of a soft starting on a single phase induction motor, which can flow the voltage and current gradually, so that it can overcome the problem of a current surge of 1.58A to 0.065A at the initial starting of the induction motor, and produce controlled motor rotation with 7 seconds to achieve, the speed of boarding at Soft Starting is set to 10 to 15 seconds. The use of Fuzzy Logic control can accelerate the Soft Starting process, so that the voltage and current can reach their nominal value 1 to 2 seconds faster than without using Fuzzy Logic control.